Early detection of Parkinson’s disease through multiplex blood and urine biomarkers prior to clinical diagnosis - Shuo Gao; Zheng Wang; Yuanfeng Huang; Guang yang; Yijing Wang; Yan Yi; Qiao Zhou; Xingxing Jian; Guihu Zhao; Bin Li; Linyong Xu; Kun Xia; et al. (npj Parkinson's Disease)
Abstract Blood and urine biomarkers are commonly used to diagnose and monitor chronic diseases. We initially screened 67 biomarkers, including 4 urine biomarkers and 63 blood biomarkers, and identified 13 blood biomarkers significantly associated with Parkinson’s disease (PD). Among these, we discovered three novel markers demonstrating strong associations: phosphate (P = 1.81 × 10−3), AST/ALT ratio (P = 8.53 × 10−6), and immature reticulocyte fraction (IRF) (P = 3.49 × 10−20). We also substantiated eight well-studied biomarkers and elucidated the roles of two previously ambiguous biomarkers. Our analyses confirmed IGF-1 (P = 7.46 × 10−29) as a risk factor, and C-reactive protein (CRP) (P = 1.43 × 10−3) as protective against PD. Genetic analysis highlighted that IRF, CRP, and IGF-1 share significant genetic loci with PD, notably at MAPT, SETD1A, HLA-DRB1, and HLA-DQA1. Furthermore, Mendelian randomization (MR) analysis suggested potential causal associations between IGF-1, CRP, and PD. We identified several blood biomarkers that may be associated with the risk of developing PD, providing valuable insights for further exploration of PD-related biomarkers.